Ultrasound Guidance Improves the Quality and Speeds Execution of Supraclavicular Brachial Plexus Block - Ershad, R; Rahman, MA; Islam, MS; Islam, MS; Hossain, MPA; Siraj, SB (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16343 JAFMC Vol.8(2) 2012 pp.22-25